Non-Hormonal Pharmacological Interventions to Manage Vasomotor Symptoms During Menopause - Hambali, Gilang Amanda; Abadi, Adnan (Sriwijaya Journal of Medicine, 2025)
This study reviews a range of non-hormonal pharmacological interventions used to treat vasomotor symptoms in postmenopausal women, including SSRIs, SNRIs, gabapentin, and neurokinin-3 receptor (NK3R) antagonists. Methods used included a literature review of multiple clinical trials and meta-analyses published over the past decade. Results showed that all interventions were effective in reducing the frequency and severity of hot flashes, with efficacy rates ranging from 36 to 72%. In addition, the side effect profile was generally mild to moderate, including nausea, sleep disturbance, and headache. NK3R antagonists, such as fezolinetant, have shown great promise with a rapid onset of action and comparable efficacy to hormone therapy, but longer-term studies are needed to assess safety. This study emphasizes the importance of an individualized approach to therapy selection and the need for monitoring liver function and potential side effects. Conclusions suggest that these non-hormonal interventions are a promising alternative for postmenopausal women for whom hormone therapy is contraindicated.